META-ANALISIS SKRIPSI MAHASISWA PENDIDIKAN FISIKA FKIP UNTAN TENTANG MODEL PEMBELAJARAN DIRECT INSTRUCTION - Teja Putri Solihan; Stepanus Sahala Sitompul; Syaiful B Arsyid (Universitas Tanjungpura, Prodi Pendidikan Fisika, 2021)
This meta-analysis aims to determine the effect of research characteristics on the effect size of the direct instruction learning model in the undergraduate thesis of the Physics Education Study Program FKIP UNTAN, published in 2016-2019. This type of research is a survey research with purposive sampling technique consisting of 6 theses. Data collection techniques in this research are documentary studies. The results of undergraduate thesis Physics Education study programs that use the direct instruction learning model obtained an average effect size of 1.00 which high effectiveness categories based on the John Hattie barometer. In this study, there are 2 characteristics of researchers examined, among others: the gender of the researcher and Grade Point Average (GPA) of the researcher. Based on the 2 characteristics of the researchers, it did not have a significant effect on the effect size of the undergraduate students' thesis in the Physics Education study program that uses the direct instruction learning model. In this study there were 13 characteristics of the methodology studied including: research location, school level, sample size, number of classes, number of meetings, material sub-fields, learning tools or media, test reliability coefficient, instrument validity, test forms, forms of research, designs experiments, and data collection tools. Of the 13 characteristics of the methodology, it did not have a significant effect on the effect size of the undergraduate students' thesis in the Physics Education study program that used the direct instruction learning model.